The legal comparison between the existing laws of provocation in Malaysia and the battered woman syndrome / Rul Iman Nur Rahidzab, Jasmine Ho Abdullah and Jainah Jaafar Sidek - Rahidzab, Rul Iman Nur; Abdullah, Jasmine Ho; Jaafar Sidek, Jainah (2014)
'Battered Woman Syndrome' is a defence used in court where the person accused of an assault or murder was suffering from battered person syndrome at the material time. Since the defence is most commonly used by women, it is usually characterised in court as battered woman syndrome or battered wife syndrome. .Currently, 'Battered Woman Syndrome' is accepted as a defence as well as mitigating factors in courts in Australia and United Kingdom. It has not been recognised in Malaysia, where courts adopt the law of provocation. In Malaysia's criminal law, provocation is a defence alleging a sudden or temporary loss of control (a permanent loss of control is in the realm of insanity) as a response to another's provocative conduct sufficient to justify an acquittal, or a mitigated sentence. However the subject of provocation must be grave and sudden and does not recognise long term abuse as a type of provocation. The provocation must not be sought by the offender as an excuse for killing or doing harm onto a person. The law, then, becomes limited and does not take into account those who lose control due to long term harassment. Since domestic violence is a prevalent problem in Malaysia, there must be a law to include the dynamics of the relationship between the victim of long term abuse and the perpetrator of the violence. Malaysia's law of provocation is inadequate to protect women who have been subject to abuse and violence compared to the law in Australia and United Kingdom since the Malaysian Penal Code does not include battered woman syndrome as part of defence for provocation. This would render women who have been subject to domestic violence to be exposed to the liability of culpable homicide in the event they have acted aggressively harming their husbands under the mental pressure of being abused domestically. Therefore a research is warranted to examine whether Malaysia should extend the laws of provocation to include the consideration of battered woman syndrome.